Tarekat Mu'tabaroh dalam Perspektif Jam'iyyah Ahlith Thoriqoh Al-Mu’tabaroh An-Nahdliyyah Indonesia - Farhan, Ibnu; Faiq, Muhammad (Mahad Aly Al Fithrah, 2023)
Spiritual phenomena are an integral part of Indonesian society. However, some think these phenomena are part of tariqa practice. This study aims to reveal the criteria and characteristics of the tariqa, especially the mu'tabaroh tariqa (notable Sufi order), through the perspective of one of the tariqa association organisations in Indonesia, namely Jam'iyyah Ahlith Thoriqoh al-Mu'tabaroh an-Nahdliyyah (JATMAN). This study is qualitative research in which the data were collected from library research. This study found that the tariqa is a path, school or order of Sufism. The tariqa is a path to get closer to Allah SWT under the guidance of a murshid (spiritual teacher). The tariqa can be categorised as mu'tabaroh if it has a connected chain (sanad) to the Prophet Muhammad and its teachings do not conflict with Islamic law. In addition, as an organisation, JATMAN, through the Ifta' Council, is competent to determine whether a tariqa can be considered mu'tabaroh or not.